Pengaruh Modal Dan Lama Usaha Terhadap Pendapatan Pedagang Online Shop (Studi Kasus Mahasiswa FISIP UNISBA Blitar) - Muhammad Nasyirudin; Dandhy Novriharyaji; Muhammad Halim Fawazi (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2021)
Today most of business people move to develop their business through online. This opens up opportunities to create incentives for business people. Social media include Facebook, Instagram, WhatsApp, Line and others. With this application, it really helps the progress of online business. The various facilities presented by the online media work wonders in the web client environment. Because it inspires everyone to become a successful online store financial expert using a smartphone for online store business advisor. The research target is to determine the effect of capital and length of business on fees earned by merchants in online stores. This type of research is survey research, using a quantitative methodology. Respondents in the study were students of online merchants FISIP UNISBA with 52 samples. The instrument used is a partial test called the T test and the F test (significance level 0.05). Measurement of the level of influence of variables using multiple linear regression and coefficient of determination using SPSS 18 program. The results of the study using the partial test (T) showed that capital had a direct and constructive effect on payments with a critical degree of 0.010 < 0.05. The length of work to get a large degree of results, namely 0.022 < 0.05. Judging from the simultaneous test (F) shows a critical degree of 0.004 <0.05. That is, the variables of capital and length of business have a positive and large effect on salaries and then increase, causing an increase in the salaries of online shop merchants.